2017
DOI: 10.1097/qai.0000000000001242
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study to Assess Individual and Structural Level Barriers Associated With Poor Retention and Re-engagement in Care Among Persons Living With HIV/AIDS

Abstract: Background Retention in care is the most challenging step along the HIV care continuum. Many patients who engage in care and achieve viral suppression have care interruptions, characterized by moving in and out of care (“churn”). Poor retention has clinical consequences and contributes to new HIV transmissions, but how to predict or prevent it remains elusive. This study sought to understand the relationship between individual- and structural-level barriers, and poor retention for persons living with HIV/AIDS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 44 publications
(37 reference statements)
1
43
0
Order By: Relevance
“…Younger patients were more vulnerable to HCI and to a gap in HIV care, in line with the findings of other studies [3,[20][21][22][23], but were less prone to permanent out-migration. It may be particularly challenging for young people to cope at once with the stigmatizing dimension of the disease, its impact on their sexual and emotional wellbeing and the necessary commitment to life-long medical care [20,24].…”
Section: Discussionsupporting
confidence: 90%
“…Younger patients were more vulnerable to HCI and to a gap in HIV care, in line with the findings of other studies [3,[20][21][22][23], but were less prone to permanent out-migration. It may be particularly challenging for young people to cope at once with the stigmatizing dimension of the disease, its impact on their sexual and emotional wellbeing and the necessary commitment to life-long medical care [20,24].…”
Section: Discussionsupporting
confidence: 90%
“…Another longitudinal study found that treatment self-efficacy also predicted medication adherence, visit adherence, CD4 cell count, and viral load (Turan et al, 2016). Three of the studies examined resilience resources that were associated with healthcare engagement and found that individual and interpersonal resources were critical to remaining engaged-in-care (Chen et al, 2013;Colasanti et al, 2017;Pecoraro et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Three articles examined resilience resources associated with healthcare engagement among PLWH. These studies suggested that PLWH who were engaged-incare had higher proactive coping (Pecoraro et al, 2016), greater HIV treatment adherence self-efficacy (Chen et al, 2013), social support (Colasanti, Stahl, Farber, del Rio, & Armstrong, 2017;Pecoraro et al, 2016), and more spirituality/religious beliefs (Pecoraro et al, 2016). However, Chen et al (2013) also found that PLWH with better healthcare provider engagement had lower self-esteem.…”
Section: Associations Between Resilience Resources and Hiv-related Oumentioning
confidence: 99%
“…The authors conclude that early assessment for predictors of poor retention could help direct interventions to high risk patients. 54 …”
Section: Synthesis Of Echpp-3 Manuscriptsmentioning
confidence: 99%